2008
DOI: 10.1002/jor.20766
|View full text |Cite
|
Sign up to set email alerts
|

Chondrogenic differentiation of adipose tissue‐derived mesenchymal stem cells: Greater doses of growth factor are necessary

Abstract: There have been controversies regarding the chondrogenic potential of adipose tissue-derived mesenchymal stem cells (ATMSCs) compared with bone marrow-derived mesenchymal stem cells (BMMSCs). The purpose of this study was to confirm the hypothesis that chondrogenesis can be achieved from ATMSCs comparable to that from BMMSCs by using greater dose of currently known chondrogenic growth factors. Chondrogenesis was induced from ATMSCs by culturing them in pellets under the following conditions: #1 without growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(78 citation statements)
references
References 34 publications
1
77
0
Order By: Relevance
“…Several in vitro studies have shown the chondrogenic differentiation of ASCs using a medium growth factor supplemented with insulin growth factor (IGF), bone morphogenetic proteins (BMPs), and transforming growth factor-β (TGF-β) [52][53][54][55]. The chondrogenic differentiation potential of ASCs was confirmed by their ability to generate cartilage in a variety of experimental models.…”
Section: Chondrogenic Differentiationmentioning
confidence: 99%
“…Several in vitro studies have shown the chondrogenic differentiation of ASCs using a medium growth factor supplemented with insulin growth factor (IGF), bone morphogenetic proteins (BMPs), and transforming growth factor-β (TGF-β) [52][53][54][55]. The chondrogenic differentiation potential of ASCs was confirmed by their ability to generate cartilage in a variety of experimental models.…”
Section: Chondrogenic Differentiationmentioning
confidence: 99%
“…This system was believed to increase stability and bioactivity of growth factors (Kim and Im, 2008;Jaklenec et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The undifferentiated mesenchymal cells can be differentiated from chondroblasts in presence of growth factors as Insulin-like growth factor (IGF), Transforming growth factor (TGF) and Bone morphogenic factor (BMP) (Erickson et al, 2002;Sheyn et al, 2008). The higher dose of these factors or combination of them was recommended to achieve this differentiation (Hennig et al, 2007;Kim and Im, 2008;Kim and Im, 2009). These growth factors have sensitivity to increased pH level, temperature and proteolysis procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with BM-MSCs, AMSCs have lower innate chondrogenesis, though high-dose combinations of growth factors (TGFβ2 and IGF-1) were capable of inducing comparable chondrogenesis in both cell types [56]. Recently, the impact of culture medium on the differentiation capacity of A-MSCs and BM-MSCs has been investigated.…”
Section: Differences Between Adipose-and Bone Marrow-derived Mscsmentioning
confidence: 99%